STRATEGI PENGEMBANGAN USAHA JASA SERVICE PADA BENGKEL MOBIL CV FUJI STAR - Dewi Rosita; Muh Sabir (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
The purpose of this study was to determine the business development strategy of CV Fuji Star service. The method used in this research is descriptive method. Descriptive method is a research method that describes the situation or occurrence of a phenomenon. By taking the descriptive method, researchers want to get a complete picture of the right strategy in developing a car service business at Cv Fuji Star. In this study, the techniques used for data collection were carried out as follows: a. Interview, namely information data obtained directly from the management of CV Fuji Star. b. Questionnaire, namely data collection techniques by asking written questions to be answered in writing by respondents. c. Documentation method, namely techniques by examining documents and reports related to research objectives. Based on the results of the SWOT analysis of the CV Fuji Star workshop service business, obtaining the ST strategy, several policy priorities need to be implemented, namely: prioritising service quality, solutions to deal with surrounding competition, and implementing an eflective waste treatment system. As for the SO strategy, namely: some key solutions for employees to be more skilled, provide guarantees to customers, and take advantage of opportunities from the growth in the number of vehicles